STUDI PEMANFAATAN TUMBUHAN OBAT BERPOTENSI MENGOBATI PADA PENYAKIT PADA PENYAKIT SISTEM PENCERNAAN DI KELURAHAN BUNUT KECAMATAN KAPUAS KABUPATEN SANGGAU - Ningsih, Kurnia; Mariani, Yeni; Arbiastutie, Yanieta; Yusro, Fathul (Universitas Tanjungpura, 2020)
The study aims to document the medicinal plants and knowledge of the use of medicinal plants used by traditional healers in Bunut Village. This research was conducted in Bunut Village, Kapuas Subdistrict, Sanggau Regency, West Kalimantan. In this study, we found a total of 31 species of medicinal plants used by traditional healers and those included in the 25 plants family. The most common family is Zingiberaceae. Herbal habitus is the most common use (51,61%). The plant part is leaves (53%) used by traditional shamans from Bunut Village. The most widely used method of processing plants is boiling (64,87%). The way of use that is often used is by drink (53%). Usage rules that are commonly used are 2x1 (65,63%). Doses of using medicinal plants are 1-3 strands/part (45%) and 4-6 strands/part (45%).Keywords: Bunut Village, Medicinal Plants, Sanggau Regency, Traditional Healer, Traditional Knowledge.